Pengarulh metode drill terhadap hasil servis panjang blullultangkis - Aini, Nurul; Nasultion, Nana Sulryana; Sulmarsono, Rhama Nulrwansyah (Universitas Hamzanwadi, 2023)
The problem of this study is the lack of maximum student ability in long service, the inaccurate method taught, the decline in student achievement due to individual players. The purpose of this study was to determine the effect of the drill method on the results of extracurricular badminton long service of MTS Sirojul Athfal students. This study uses a quantitative approach method with a pre-experimental technique of one groulp pretest-postest design and the sampling technique uses pulrposive sampling. The population in the study was 24 students who participated in blullultangkis extracurricular activities consisting of 13 female students and 11 male students where the entire population was sampled. Data analysis techniques use descriptive statistics, then SPPS application processing is carried out. Based on the results of the research that has been obtained by data analysis and hypothesis testing from the average before the treatment and after the treatment has increased significantly from 38.25 to 80.71. Meanwhile, the results of hypothesis testing calculations obtained a significant value that is less than the significant level (α) which is 0.0001 < 0.05. The conclusion is that there is a drill method influence in improving the results of long serve blullultangkis extracurricular students of MTS Sirojull Athfal.